2017
DOI: 10.1186/s12870-017-0973-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis reveals the transcriptional alterations in heat-resistant and heat-sensitive sweet maize (Zea mays L.) varieties under heat stress

Abstract: BackgroundDespite the heat-related physiology and heat-shock proteins in maize have been extensively studied, little is known about the transcriptome profiling of how the maize varieties with different genotypes responding to high temperatures. Seedling mortality of Xiantian 5 (XT) is significantly lower than that of Zhefengtian (ZF) when exposed to high temperature (42 °C for 6 h) and followed by a recovery growth (25 °C for one week). Therefore, we performed a transcriptome analysis using the total RNA extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 33 publications
10
60
0
Order By: Relevance
“…CYPs catalyzed a broad range of oxidative substances, including insecticides, plant secondary metabolites, and some oxidative substances induced by heat exposure (Daborn et al, 2007;Niu et al, 2011). In the present study, upregulation of CYPs in M. alternatus, similar to other organisms treated with heat stress, certified this role of CYPs Shi et al, 2017). In addition to CYPs, organisms produced ALDHs in response to a suite of environmental stresses that perturb metabolism, including salinity, dehydration, desiccation, and cold and heat shock (Kirch et al, 2004).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…CYPs catalyzed a broad range of oxidative substances, including insecticides, plant secondary metabolites, and some oxidative substances induced by heat exposure (Daborn et al, 2007;Niu et al, 2011). In the present study, upregulation of CYPs in M. alternatus, similar to other organisms treated with heat stress, certified this role of CYPs Shi et al, 2017). In addition to CYPs, organisms produced ALDHs in response to a suite of environmental stresses that perturb metabolism, including salinity, dehydration, desiccation, and cold and heat shock (Kirch et al, 2004).…”
Section: Discussionsupporting
confidence: 52%
“…De novo transcriptome assembly has been widely applied to detect and identify differential genes under different experimental conditions (He et al, 2017;Liu et al, , 2018Chen et al, 2018), enabling researchers to understand the molecular mechanism of action from a transcriptomics perspective. Different expression gene (DEGs) profiling in this technique presents the advantages of precision, economy, and repeatability, and has been widely used in plants to explore genes related to heat resistance (Li et al, 2015;Yan et al, 2016;Shi et al, 2017), while in insects, comparative transcriptome analysis related to heat responses has been only applied in several species, including G. pyloalis, Cryptolaemus montrouzieri, and Bombyx mori (Wang et al, 2014;Zhang Y.H. et al, 2015;.…”
Section: Introductionmentioning
confidence: 99%
“…This result suggested that EPT process was a stimulus process compared to an appropriate temperature. Similar results were reported on Populus euphratica Oliver (Chen et al, 2015), Chrysanthemum (Sun et al, 2015), rice (Wu et al, 2015) and sweet maize (Shi et al, 2017) when subjected to heat stress. A few DEGs were observed to be annotated to GO terms of aromatic compound biosynthetic process, aromatic amino acid family metabolic process and cellular aromatic compound metabolic process, betaglucosidase activity, glucosidase activity and malate dehydrogenase activity as well as KEGG pathways of starch and sucrose metabolism, biosynthesis of secondary metabolites, pentose and glucuronate interconversions, carotenoid biosynthesis, metabolic pathways and galactose metabolism which indicated that these genes involved in aroma production and sugar/ acid metabolism were differentially expressed in the EPT process.…”
Section: Discussionsupporting
confidence: 85%
“…Transcriptomic changes drive the physiological response to progressive drought stress and rehydration in tomato [236]. In a recent study, comparative transcriptome analysis revealed the transcriptional alterations in heat-resistant and heat-sensitive sweet maize (Zea mays L.) varieties under HS [237]. Chen and Li [238] found that DEGs were responsible for HS and protein folding in Brachypodium distachyon.…”
Section: Development Of Hs-tolerance Plants Using Omics Approachesmentioning
confidence: 99%